Introduction of a secondary ligand into titanium-based metal–organic frameworks for visible-light-driven photocatalytic hydrogen peroxide production from dioxygen reduction. Issue 5 (15th January 2021) - Chen, Xiaolang; Kuwahara, Yasutaka; Mori, Kohsuke; Louis, Catherine; Yamashita, Hiromi
Abstract : The introduction of a secondary ligand into titanium-based metal–organic frameworks for visible-light-driven photocatalytic H2 O2 production from dioxygen reduction. Abstract : The introduction of multiple components with specific properties into metal–organic frameworks (MOFs) is an attractive strategy to modify their catalytic properties. Herein, through the introduction of the ligand 4, 4′, 4′′, 4′′′-(pyrene-1, 3, 6, 8-tetrayl)tetrabenzoic acid (L2) into MIL-125 during its synthesis, four L2-functionalized titanium-based MOFs, MIL-125- x L2 ( x = 0.035, 0.07, 0.14, and 0.21), were successfully prepared for the first time. Due to the introduction of the L2 ligand, the morphology of MIL-125- x L2 crystallites changed from a plate to an octahedron, and these MOFs contained more structural defects of missing ligands and possessed slightly larger BET surface areas and pore volumes. Most importantly, MIL-125- x L2 achieved a high photoactivity for H2 O2 production from the dioxygen (O2 ) reduction reaction that cannot be catalyzed by pristine MIL-125. The most active MIL-125-0.14L2 displayed a remarkable H2 O2 production rate of 1654 μmol L −1 h −1 under visible-light irradiation ( λ > 400 nm) using triethanolamine as a sacrificial agent. Such high activity can be attributed to the unique visible light absorption ability of L2, which originates from the large aromatic ring consisting of an extended π-electron system, making MIL-125- x L2 a visible-light-driven catalyst. This work provides an effective strategy for the design of multi-functional MOFs and enriches the application of MOFs in the field of new energy production.